Spatial distribution, tree host associations, and deforestation threats on two stingless bee species in the Peruvian Amazon - Demetrio, Richar (2025)
Background: Stingless bees (Apidae: Meliponini) are critical pollinators in the Peruvian Amazon, sustaining biodiversity, crop productivity, and indigenous livelihoods. Despite their ecological and economic importance, the effects of deforestation and illegal logging on their populations remain poorly understood. Nesting tree loss, habitat fragmentation, and changes in elevation influence stingless bee distribution, yet conservation efforts remain insufficient due to a lack of spatial data on their vulnerability. Results: This study examines the spatial distribution, elevation trends, and deforestation threats affecting Melipona eburnea and Tetragonisca angustula, with a focus on tree nesting preferences in the Biosphere Reserve Avireri-Vraem. Using literature reviews, field observations, and GPS surveys, we assessed species distribution patterns, deforestation risks, and nesting tree associations. Our findings reveal that over 50% of their habitats overlap with high deforestation risk zones, largely driven by illegal logging of key nesting trees. Elevation analysis indicates species-specific adaptations, with M. eburnea predominantly in lowland regions, while T. angustula is more frequent at higher altitudes. GPS fieldwork identified strong associations with specific host trees, notably Guarea guidonia and Ficus insipida, with larger trees (> 60 cm DBH) serving as critical nesting sites. Several of these, including Aniba gigantiflora and Cedrelinga cateniformis, are among the most ilegally harvested species, intensifying threats to bee populations. Conclusions: Deforestation-driven habitat loss and fragmentation pose an immediate threat to stingless bee populations by reducing nesting availability, limiting pollination networks, and disrupting genetic exchange. Our findings emphasize the urgent need for targeted conservation strategies, including the preservation of key nesting trees, the establishment of biological corridors, and the promotion of sustainable forestry practices. Given the role of stingless bees as keystone pollinators, their protection is crucial for maintaining biodiversity and ecosystem stability. Recognizing stingless bee habitats under a Rights of Nature framework would provide a legal mechanism to safeguard their nesting sites from further exploitation. Furthermore, strengthening community-led conservation efforts in high-risk areas can enhance long-term resilience. This study provides a baseline for future conservation policies, bridging scientific data and indigenous knowledge to protect Amazonian stingless bees and their ecosystems.